A Middle Palaeolithic burial of a modern human at Taramsa Hill, Egypt - Vermeersch, P. M.; Paulissen, E.; Peer, P. Van; Stokes, S.; Charlier, C.; Stringer, C.; Lindsay, W.
Discussion about a possible African origin of modern humans is hampered by the lack of Late Pleistocene skeletal material from the Nile valley, the likely passage-way from East Africa to Asia and Europe. Here we report the discovery of a burial of an anatomically modern child from southern Egypt. Its clear relation with Middle Palaeolithic chert extraction activities and a series of OSL dates, from correlative aeolian sands, suggests an age between 49,800 and 80,400 years ago, with a mean age of 55,000.